2006
DOI: 10.1375/twin.9.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Twins Delivery; Predictors for Successful Vaginal Delivery: A Single Center Experience

Abstract: The aim of this study was to compare maternal and neonatal outcome of twin births according to mode of delivery and to isolate the factors predicting a successful vaginal delivery and those predicting a failed trial of labor (TOL) leading to an emergent cesarean section. We reviewed all twin deliveries during the years 1995 to 2004. Parameters studied include maternal age, parity, gestational age, maternal antepartum complications and postpartum complications, fetal presentations, birthweight, mode of delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…After multivariate analysis, independent risk factors of CS were nulliparity and non‐cephalic presentation of the second twin. Of these, nulliparity showed the strongest relation to unsuccessful vaginal twin delivery, as has previously been reported 17‐22 …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…After multivariate analysis, independent risk factors of CS were nulliparity and non‐cephalic presentation of the second twin. Of these, nulliparity showed the strongest relation to unsuccessful vaginal twin delivery, as has previously been reported 17‐22 …”
Section: Discussionsupporting
confidence: 71%
“…Of these, nulliparity showed the strongest relation to unsuccessful vaginal twin delivery, as has previously been reported. [17][18][19][20][21][22] Although a non-cephalic second twin was found to be an independent risk factor of CS, as many as 76.1% of the C/NC group cases achieved vaginal birth and perinatal outcomes were comparable in the C/C and C/NC groups. Therefore, in the light of these results, TOL can be a favorable option for twin pregnancies with a non-cephalic second twin if the parturient is oriented towards TOL.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A randomized controlled trial conducted in the 1980s that investigated planned vaginal birth versus cesarean section for vertex‐nonvertex twins showed that the outcome of the second twin was not significantly affected by mode of delivery . These findings have been supported by others, concluding that morbidity and mortality are not significantly different when comparing vaginal and cesarean delivery of vertex‐nonvertex twins, except when the first twin is in breech position .…”
mentioning
confidence: 84%
“…This study showed 67% of breech twins were delivery via emergency CS, a higher rate than that expressed in other studies 12. A larger randomized study is necessary to justify a policy of routine elective CS delivery of twins.…”
Section: Resultsmentioning
confidence: 50%